1991
DOI: 10.1288/00005537-199102000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cytokines present in middle ear effusions

Abstract: Retention of inflammatory mediators and cells in the middle ear cleft during chronic otitis media with effusion (COME), results in ongoing inflammation with the potential for pathologic changes and hearing loss. Cytokines are glycoproteins produced by macrophages and other cells. Activities of cytokines include fever production, osteoclast, fibroblast, phagocyte and cytotoxic cell activation, regulation of antibody formation, and inhibition of cartilage, bone and endothelial cell growth. Using enzyme-linked im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
126
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(132 citation statements)
references
References 9 publications
5
126
1
Order By: Relevance
“…Interleukin 1A (IL-1A) is one of the important cytokines in the inflammatory process. The level of IL-1A in endolymph increases after noise exposure (12) or during otitis media (13,14). It is also well known that sensory neural hearing loss and M Ménière's disease are aggravated during systemic infection (15Y17).…”
mentioning
confidence: 99%
“…Interleukin 1A (IL-1A) is one of the important cytokines in the inflammatory process. The level of IL-1A in endolymph increases after noise exposure (12) or during otitis media (13,14). It is also well known that sensory neural hearing loss and M Ménière's disease are aggravated during systemic infection (15Y17).…”
mentioning
confidence: 99%
“…In children, many studies have demonstrated the involvement of immune reactions and/or eustachian tube dysfunction induced by bacterial infections in the middle ear and/or nasopharynx in the pathogenesis of OME (4,10,13,14,16,30,31). To date, several inflammatory cytokines such as interleukin 1 (IL-1), IL-2, IL-6, IL-8, and tumor necrosis factor alpha (TNF-␣) are observed in middle ear effusions (MEEs) (13,30,31). In addition, bacterial DNAs and components such as endotoxins are also detected in MEEs, whereas bacterial culture from MEEs is often negative (4,10,16).…”
mentioning
confidence: 99%
“…88 The analysis of peripheral blood immunologic pattern in patients with persistent middle ear effusions 89,90 showed the following: (1) the number of CD4…”
Section: T Cells Activated Cd8mentioning
confidence: 99%